1993
DOI: 10.1002/jbm.820270116
|View full text |Cite
|
Sign up to set email alerts
|

A histological and histomorphometrical investigation of fluorapatite, magnesiumwhitlockite, and hydroxylapatite plasma‐sprayed coatings in goats

Abstract: Plasma-sprayed ceramic coatings of fluorapatite (FA), magnesiumwhitlockite (MW), and hydroxylapatite (HA), and noncoated Ti-6Al-4V alloy (Ti) implants were evaluated histologically and histomorphometrically in a goat animal study. Cylindrical Ti-6Al-4V plugs were plasma-spray-coated with FA, MW, and HA. Noncoated, grit-blasted Ti plugs served as controls. The plugs were implanted into the right femur and left humerus of 20 adult goats. The results were evaluated using descriptive histology and histomorphometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(187 citation statements)
references
References 24 publications
13
163
1
3
Order By: Relevance
“…Since then numerous reports have been published about the osteoconductive properties of CaP-coated implants (osteoconduction refers to the ability of a biomaterial to support the growth of bone over its surface). These CaP coatings are described to induce an increased bone-to-implant contact (38,(43)(44)(45), to improve the implant fixation (46), and to facilitate the bridging of small gaps between implant and surrounding bone (47,48). As an example of the osteoconductive properties of CaP coatings, Fig.…”
Section: Calcium Phosphate Coatingsmentioning
confidence: 99%
“…Since then numerous reports have been published about the osteoconductive properties of CaP-coated implants (osteoconduction refers to the ability of a biomaterial to support the growth of bone over its surface). These CaP coatings are described to induce an increased bone-to-implant contact (38,(43)(44)(45), to improve the implant fixation (46), and to facilitate the bridging of small gaps between implant and surrounding bone (47,48). As an example of the osteoconductive properties of CaP coatings, Fig.…”
Section: Calcium Phosphate Coatingsmentioning
confidence: 99%
“…Several studies have demonstrated these properties either with osteoblast cultures 5,20 or with in vivo experiments 3,4,11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally reported in the literature that ceramic coatings improve the osseointegration of metallic scaffolds by promoting the filling of gaps between bone and implant 12 , enhancing bone contact with the implant surface 11,28 and possessing osteoinductive properties 29,30 . However, the results of experimental studies comparing titanium implants with and without ceramic coatings have conflicting results, with evidence either of lack of benefit [31][32][33][34][35] or superior results 11,12,28,36 with bone growth acceleration 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations